Penerapan Digital Bisnis Dan Promosi Pada Umkm Hasta Catering - Abrida Triandini Hasta; Firdha Aulia Haryadi; Tri Ghina Ashyla (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
In the modern technological era, digitalization plays a crucial role in the development of businesses, including service industries such as catering. This study investigates the implementation of digital solutions in Hasta Catering to enhance operational efficiency and provide an excellent customer experience. Firstly, an assessment of a digital order management system allowing customers to place orders online is conducted. Additionally, the integration of delivery tracking technology ensures the accuracy of catering order deliveries. Secondly, the analysis of customer data and preferences through digital platforms is utilized to optimize menus and provide personalized options, thereby increasing customer satisfaction and expanding market share. As a result, the digitalization of Hasta Catering business demonstrates a significant improvement in operational efficiency, reduction in order errors, and enhanced customer retention. This study provides insights for similar businesses to adopt digital strategies for sustainable growth.